Autogenous Tensor Fascia Lata Graft Replacement of the Patellar Ligament in a Dog - Aron, D. N.; Selcer, B. A.; Smith, J. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
This report documents a complicated trauma case in a dog that was successfully managed by substitution of a missing patellar ligament with an autogenous tensor fascia lata free graft. Important to the success of the case was the use of a careful postoperative regime of progressive controlled mobilization with the aid of the hinged transarticular external skeletal fixator. Because of the advantages provided by use of the autogenous tensor fascia lata graft and the hinged transarticular external skeletal fixator, patient morbidity was low and the end result was good.An autogenous tensor fascia lata free graft was successfully used to completely substitute for a missing patellar ligament in a dog. Postoperative rehabilitation was facilitated by the use of the hinged transarticular external skeletal fixator. The technique is described along with the results. Complete substitution of the patellar ligament with a graft has not been reported in the dog.
Keywords: Patellar ligament; graft; controlled mobilization; dog